Measuring pressure during coronary artery angiography in ex-vivo hearts. (March 2016) - Robinson, C.; Adnan, A.; Adlam, D.; Biggs, M.; Rutty, G.; Morgan, B.
Abstract: Coronary artery disease (CAD) is the most common cause of sudden adult death. Diagnosis in life and after death is therefore crucial, but can be problematic and inaccurate. Post-mortem CT angiography (PMCTA) is attempting to address this, but its accuracy is still not fully established. In clinical practice, pressure measurements, recording drops in pressure across the stenosis, are now being used to determine physiological significance, as the degree of narrowing on imaging can be misleading. This study was designed to investigate the introduction of pressure measurement to PMCTA in order to understand the importance of re-pressurising vessels in the evaluation of CAD. Ex-vivo porcine hearts were used to develop the technique. Methods to introduce catheters and wires were investigated and a system was developed to suspend the heart, to enable pressure tests and CT scans. Consistent measurable pressures were achieved with good correlation of measured arterial pressure to delivered pressure in most cases. Pressure measurements were shown to be inaccurate in decomposed hearts, poor dissection and cannulation damaging the vessel, contamination of the vessels (e.g. by air) and malposition of the pressure measurement wire. Highlights: Pressure change across a stenosis is more informative than radiographic appearance. This study describes a means to measure pressure during PMCTA. Consistent measurable pressures can be achieved.